2014
DOI: 10.1007/s10661-014-3653-5
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of the relationship between various waterscapes and outdoor activities: Edirne, Turkey

Abstract: The environment is very important in terms of the behaviours and actions of human beings, and activity-environment correlation is used frequently in outdoor arrangements. The environment must meet the requirements and expectations of society. Outdoor activities are the activities that contribute to the well-being of human beings in physical (heartbeat, respiration, blood pressure, etc.) (Ulrich, Journal of Environmental Psychology 11:210-230, 1991), psychological (fear, anxiety, depression, loneliness, stress,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 27 publications
0
2
0
2
Order By: Relevance
“…The waterside areas of urban blue spaces are particularly stimulating for dynamic activities, and it is indicated that living closer to waterscapes will be associated with higher levels of physical activity [54,74,96], such as walking, exploring, talking, and relaxing, which has the same positive impact on people's mental health as being active in urban green spaces [49]. Additionally, several respondents living within four neighborhoods in two coastal towns mentioned their preference for three types of social dynamics, each of which was evident in waterscapes: (a) seeking friendly conversation and a joyful atmosphere, (b) engaging in spaces that offering a variety of opportunities for family leisure and wellbeing, and (c) bonding relationship through shared hobbies and experiences [32].…”
Section: The Psychological Benefits Coming From Exercising In Waterscapesmentioning
confidence: 99%
“…The waterside areas of urban blue spaces are particularly stimulating for dynamic activities, and it is indicated that living closer to waterscapes will be associated with higher levels of physical activity [54,74,96], such as walking, exploring, talking, and relaxing, which has the same positive impact on people's mental health as being active in urban green spaces [49]. Additionally, several respondents living within four neighborhoods in two coastal towns mentioned their preference for three types of social dynamics, each of which was evident in waterscapes: (a) seeking friendly conversation and a joyful atmosphere, (b) engaging in spaces that offering a variety of opportunities for family leisure and wellbeing, and (c) bonding relationship through shared hobbies and experiences [32].…”
Section: The Psychological Benefits Coming From Exercising In Waterscapesmentioning
confidence: 99%
“…In Great Britain, the Sustainable Urban Drainage System (SUDS) [46] has been used since the 1980s. The existing typologies representing the types of water objects used in contemporary design of public spaces are insufficient and require deepening, hence the main goals of the presented study [47][48][49]. It is assumed that water elements in public spaces are associated with values important for users, making a given place more attractive and better identifiable in the city structure [12,50,51].…”
Section: Introductionmentioning
confidence: 99%
“…Bu alanlarda insanların içinde bulundukları ortamlardan önemli ölçüde etkilendiği ve daha da önemlisi, içinde bulundukları ortamın mutluluk durumlarını etkilediği bilinmektedir. Bu etkinin nedenleri, esas olarak bu tür ortamları oluşturan mekânsal elemanların ve bileşenlerin özellikleri ve görünüşleridir [4]. Bu nedenle kent parkları kent ekosistem ağının önemli bir parçasını oluşturarak kentin ekosistemine katkı sağlamaktadır.…”
Section: Introductionunclassified